Mating or marrying, which? (Rev. and enl. from an address delivered by the author before Lucifer Circle of Chicago in October 1896 [...]). - [W.H. van Ornum, A lesson from history. (Rev. and republ. from the Twentieth Century). - W.H. van Ornum, The problem of criminality (Free society publishing Co., 1898)
Free society library, May 1898, no 5.